Continuous Compliance on AWS (The DevSecOps on AWS Series) - Duvall, Paul (Addison-Wesley Professional, 2020)
6+ Hours of Video Instruction Automatically adhere to best practices by learning to run compliance as code in a Continuous Delivery process using AWS Config Rules, Amazon CloudWatch Event Rules, AWS CloudFormation, AWS CodePipeline, and AWS Lambda. Overview In this course, you will learn to use AWS services to define compliance as code, including AWS Config Rules, Amazon CloudWatch Event Rules, AWS CloudFormation, AWS CodePipeline, and AWS Lambda. You also learn how to use a combination of these tools to prevent, detect, and remediate noncompliant resources in your software systems. Paul Duvall has six AWS certifications, including AWS Certified DevOps Engineer Professional and AWS Certified Security ,Äì Specialty. He has architected, implemented, and managed software and systems solutions for more than 20 years. Throughout the course, you will have the opportunity to work along with Paul as he demonstrates how to automate the provisioning of these services and how to include them as part of a deployment pipeline using AWS CloudFormation and AWS CodePipeline. About the Instructor Paul Duvall is a founder of Stelligent and Chief AWS Evangelist at Mphasis,Äìan AWS Premier Consulting Partner with the DevOps, Security, and Financial Services Competencies that has been implementing Continuous Delivery solutions on AWS since 2009. Paul has been an AWS Community Hero since 2016. He has six AWS certifications, including AWS Certified DevOps Engineer Professional and AWS Certified Security ,Äî Specialty. He has architected, implemented, and managed software and systems solutions for more than 20 years. He is the principal author of Continuous Integration: Improving Software Quality and Reducing Risk (Addison-Wesley, 2007), a 2008 Jolt Award Winner, and author of many other publications, including DevOps Essentials on AWS LiveLessons (Addison-Wesley, 2017). He writes for several publications including Forbes , Stelligent , and Mphasis , and hosts the "DevOps on AWS Radio" podcast. Skill Level Intermediate to Advanced Learn How To Apply key compliance concepts on AWS. Use AWS services and tools to automate compliance, including AWS CloudFormation, AWS Config Rules, AWS CodePipeline, Amazon CloudWatch Event Rules, and AWS Lambda. Integrate Continuous Compliance workflows for prevention, detection, and remediation into your software delivery process. Who Should Take This Course Software developers and security and compliance professionals who...